Promoting and protecting the rights of the elderly in Malaysia: guidance from the International Human Rights Law and experience of other countries / Husna Fauzi - Fauzi, Husna (2014)
The ageing of population is a worldwide phenomenon which is occurring in most countries of the world and Malaysia is not an exception. Globally, the population of older persons is growing by two per cent each year, considerably faster than the general population as a whole. By 2050, the number of older persons in the world is projected to exceed the number of young for the first time in history. 1The United Nations Committee on Economic, Social and Cultural Rights has identified the elderly as a vulnerable group which requires specific attention and needs. Realising that the elderly are in a vulnerable position and at risk to various forms of abuse and exploitation, there has been an increased concern among the international community in recent years, for the creation of an international convention on the rights of the older persons. Having an international convention that tailored to the particulars needs of older persons is seen as an essential tool in promoting and protecting the rights of the elderly. In recognition that the Malaysian elderly population too has steadily increased over the years, it is therefore considerably significant that the interests and rights of this special group of population is to be given due attention. Against this background, this paper aims to provide an overview on the existing laws that protect and promote human rights of the elderly in Malaysia, within the context of the rights proclaimed by the international and regional human rights instruments. The paper begins with the brief accounts on the trend of population ageing in Malaysia. This is followed by the discussion on the status of the elderly within the framework of the international and regional human rights instruments. Malaysia‟s commitments on the elderly issues will also be highlighted. Reference will also be made to selected countries which have enacted elderly specific legislation as one of the mechanisms in protecting the rights of their older persons. Finally, the paper ends with some recommendations to be adopted in safeguarding the rights and interests of the Malaysian elderly so that they too can enjoy human rights guaranteed to the other members of the society.